Analyzing The Impact of Online Marketing on Students' Purchase Decisions on Shopee E-Commerce in Tasikmalaya, Indonesia - Lati Sari Dewi; Risman Barkah (Research Synergy Foundation, 2024)
The study was driven by the growing trend of online shopping among students and the need to understand how digital marketing strategies impact their purchasing decisions on e-commerce platforms like Shopee. This research aims to evaluate the influence of online marketing on the purchasing decisions of students at STIE Latifah Mubarokiyah Suryalaya, in Tasikmalaya, Indonesia, specifically using the Shopee platform. Online marketing facilitates the transaction of goods and services via the Internet, providing the convenience of shopping without time and space constraints and allowing consumers to select products based on their preferences. The study employs a descriptive quantitative approach, involving 77 respondents selected through purposive random sampling. Data collection includes both primary and secondary sources, which are analyzed using simple regression, correlation analysis, determination analysis, and hypothesis testing. The findings reveal that online marketing strategies significantly influence students' purchasing behaviour on e-commerce platforms, with a correlation coefficient of 0.694 and a determination coefficient of 48.1%. This indicates that nearly half of the variability in student purchase decisions can be attributed to online marketing strategies. Moreover, the study offers new insights into how specific online marketing tactics, such as targeted advertisements and social media promotions, uniquely influence student preferences and purchasing patterns. These findings highlight the importance of personalized marketing approaches in shaping consumer behaviour. The study also suggests that further research should explore additional factors influencing consumer behaviour in e-commerce to achieve a more comprehensive understanding.